Extension of a Coronary Intramural Hematoma as a Complication of Early Percutaneous Coronary Intervention after Thrombolytic Therapy - Mohamed El-Mawardy; Mohamed Abdel-Wahab; Gert Richardt (Case Reports in Medicine)
The optimal treatment approach for coronary intramural hematomas has not been well defined, and discussion is limited to scarce data. In addition, the impact of prior thrombolytic therapy in the setting of coronary artery dissections with possible development and/or extension of an intramural hematoma is not well understood. We describe a case of iatrogenic periprocedural dissection of the left anterior descending artery (LAD) with development of an intramural hematoma and the extension of this hematoma to the left main (LM) and left circumflex (LCX) arteries in a middle-aged female, where prior recent thrombolytic therapy may have played a role in its triggering or facilitation of its extension. This case highlights the importance of facilitation of bleeding complications by prior use of thrombolytic therapy not only peripherally but intracoronary too and the use of intravascular ultrasound for both diagnosis, followup, and percutaneous coronary intervention (PCI) guidance.